Falls from high-altitude with no fatal injuries: Report of two autopsy cases - Tomoka Yamaguchi; Shiori Hattori; Keisuke Mizuo; Satoshi Watanabe (Forensic Science International: Reports, 2024)
We report two cases of falls from a very high altitude with no fatal injuries. Two men were found dead directly under a high bridge. Surveillance video footage indicated that they had fell approximately 120 m from the bridge to the ground. On the fall site, there was snow on the ground, and the men were completely buried in the snow. An autopsy performed at 2 days after their bodies were found, showed a small subdural hematoma in one patient and a minor pulmonary laceration in the other. However, no fatal injuries were observed. Their deaths were caused by hypothermia based directly on the difference in the coloration of the left and right cardiac blood, the bright red to reddish brown lungs, and the Wischnewski spots. The reason why no fatal injuries occurred despite falling from height was considered to be the fall onto the snow.